Describing objectively measured intensive care nurses' physical work activity behavioural patterns during a 12‐hr shift. Issue 21 (12th September 2020) - Yu, Fiona; Narayanan, Anantha; Mackay, Lisa; Ward, Kim; King, Anna; Smith, Melody
Abstract: Aim and objectives: To describe intensive care unit (ICU) nurses' physical work activity behavioural patterns over 12 hr using dual accelerometry, following a job demands–recovery framework. Background: Limited studies utilised accelerometry to objectively analyse nurses' physical workloads. Little is known about intensive care nurses' physical activity patterns during a 12‐hr shift. Design: A cross‐sectional study was conducted with intensive care nurses from four units in Auckland, New Zealand. Methods: Each participant wore two Axivity AX3 accelerometers to measure physical activity during a 12‐hr day or night shift. An online survey captured participants' demographic information. R software (version 3.6.1) and SPSS version 26 were utilised for data analysis. The STROBE was followed. Results: A total of 102 nurses were included in this study. A high level of light intensity activity behaviours (standing, dynamic standing, walking) was observed throughout the day shifts, with no higher intensity behaviours identified. Activity levels were highest at the beginning of shifts and followed a consistent pattern, with an additional peak around midday for day shifts and at the end of the shift for night shifts. Observable differences were seen between day and night shifts with a greater prevalence of sitting and lying during night shifts. Standing, dynamic standing, sitting, lying and walking were significant factors in the differences of the physical work behaviours between the day shift nurses and the night shift nurses. Significant differences in dynamic standing and lying were found between ICUs. Conclusions: Intensive care nurses' physical work activity involved a large amount of standing and dynamic standing during a 12‐hr shift. The overall physical workload during a 12‐hr day shift was significantly higher than that during a 12‐hr night shift. Relevance to clinical practice: Results may help managers attain a better understanding of nurses' physical workloads during a 12‐hr shift.